Partitive Determiners, Partitive Pronouns and Partitive Case - Sleeman, Petra; Giusti, Giuliana (Linguistische Arbeiten, 2021)
The fine-grained morpho-syntactic and semantic variation displayed by partitive elements across European languages is far from being well-described, let alone well-understood. This volume focuses on Partitive Determiners, Partitive Pronouns and Partitive Case in European languages, their emergence and spread in diachrony, their acquisition by L2 speakers, and their syntax and interpretation in a cross-theoretical typological perspective.